Multifunctional coating material with super-hydrophilicity and preparation method thereof

A multifunctional coating material with enhanced hydrophilicity, antibacterial, and aging resistance is achieved through a specific composition and preparation process, addressing the limitations of existing coatings.

CN119242157AActive Publication Date: 2025-01-03JIAXING SHAWEI DOPE CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411598689.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-03
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

Existing coating materials lack sufficient antibacterial and aging resistance despite having hydrophilicity, limiting their effectiveness and market suitability.

Method used

A multifunctional coating material composed of polyurethane resin, functional additives, synergistic additives, surfactants, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and water, prepared through specific mixing and treatment processes, including the use of functional additives and hollow carbon nanospheres, to enhance hydrophilicity, antibacterial properties, and aging resistance.

Benefits of technology

The coating material achieves good super hydrophilicity, excellent antibacterial resistance, and effective aging resistance, ensuring quality and broad market applicability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of hydrophilic materials, in particular to a multifunctional coating material with super hydrophilicity and a preparation method thereof. The multifunctional coating material is prepared from the following raw materials in parts by weight: 30-40 parts of polyurethane resin, 3-6 parts of a functional aid, 3-5 parts of a synergistic aid, 2-4 parts of a surfactant, 4-7 parts of lauryl sodium sulfate, 4-7 parts of sodium dodecyl benzene sulfonate and 50-60 parts of water, the preparation method comprises the following steps: mixing polyurethane resin, a functional auxiliary agent, a synergistic auxiliary agent, lauryl sodium sulfate, sodium dodecyl benzene sulfonate and water in mixing equipment, adding a surfactant for treatment, discharging after the materials are mixed, and then inspecting and metering to finally prepare a multifunctional coating material finished product with super hydrophilicity. The multifunctional coating material with the super-hydrophilicity prepared by the invention not only has better super-hydrophilicity, but also has excellent antibacterial and anti-aging properties, and the quality of the multifunctional coating material is effectively ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrophilic materials, in particular to a multifunctional coating material with super hydrophilicity and a preparation method thereof. Background Art

[0002] Coating materials play a key role in many fields. In the field of construction, the coating of the building facade can play a dual function of decoration and protection, preventing rain erosion and ultraviolet radiation from damaging building materials and extending the service life of building materials. In the automotive industry, automotive coatings can not only make the appearance of the car more beautiful, but also resist the corrosion of the car body by environmental factors such as acid rain and sandstorms. In the field of electronic equipment, coatings can be used to protect circuit boards to prevent pollutants such as moisture and dust from affecting the performance of electronic components.

[0003] In the patent document with application number "CN201810671465.8" and name "A super-hydrophilic coating agent and its preparation method", it is recorded that "the super-hydrophilic coating agent of the present invention contains the following ingredients: resin, hydrophilic surfactant, modified nanoparticles, leveling agent, dispersant, solvent. The super-hydrophilic coating agent of the present invention can make the surface of the substrate rough, which is more conducive to the spreading of water and has better hydrophilicity. It also has the advantages of ultra-thinness, high hardness, erosion resistance and fast film formation. The method for preparing the super-hydrophilic coating agent provided by the present invention has low process conditions, simple operation, and does not require UV curing."

[0004] Although the coating material manufactured by the above patent document has certain advantages such as hydrophilicity, its antibacterial and aging resistance properties are relatively insufficient and still need to be further improved. Based on this, the present invention provides a multifunctional coating material with super hydrophilicity and a preparation method thereof to solve the above technical problems. Summary of the invention

[0005] The purpose of the present invention is to provide a multifunctional coating material with super hydrophilicity and a preparation method thereof. The prepared multifunctional coating material with super hydrophilicity not only has good super hydrophilicity performance, but also has excellent antibacterial and aging resistance, effectively ensuring its quality.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a multifunctional coating material with super hydrophilicity, which is composed of the following raw materials in parts by weight: 30 to 40 parts of polyurethane resin, 3 to 6 parts of functional additives, 3 to 5 parts of synergistic additives, 2 to 4 parts of surfactants, 4 to 7 parts of sodium dodecyl sulfate, 4 to 7 parts of sodium dodecylbenzene sulfonate and 50 to 60 parts of water.

[0008] The present invention is further configured as follows: the preparation process of the functional additive is as follows:

[0009] Put tetraethyl orthosilicate in anhydrous ethanol at a mass ratio of 1:2.8-3.2, stir and mix for 10-15 minutes at 55-58°C and 100-120r / min, then add compound liquid, 25% ammonia water and eugenol to the obtained mixture, continue stirring for 5-8 minutes, and keep warm for 8-10 hours;

[0010] Then, after centrifugation at a speed of 5200-5400 r / min for 20-25 minutes, the obtained centrifugal product is washed 2-4 times with anhydrous ethanol, dried and ground to obtain a functional additive.

[0011] The present invention is further configured as follows: the first compound liquid is mixed with γ-aminopropyltriethoxysilane and water in a mass ratio of 1:12-14, and the addition amount of the first compound liquid is 2.5-4.2% of the mass of the mixed liquid.

[0012] The present invention is further configured as follows: the amount of ammonia water added is 2.8-3.5% of the mass of the mixed solution, and the amount of eugenol added is 1.8-3.1% of the mass of the mixed solution.

[0013] The present invention is further configured as follows: the preparation process of the synergistic aid is as follows:

[0014] Aluminum chloride hexahydrate was added into deionized water at a dosage ratio of 0.8 to 1.2 g / mL, stirred at 120 to 220 r / min for 20 to 30 min, and then pretreated hollow carbon nanospheres were added thereto, and treated at 7000 to 8000 r / min for 40 to 46 min;

[0015] Then, the pH value is adjusted to 8.8-9.2 with aqueous ammonia, filtered, washed to neutrality, dried, placed in a nitrogen atmosphere, treated at 880-900° C. for 14-16 hours, and cooled to obtain a functional additive.

[0016] The present invention is further configured as follows: the preparation process of the pretreated hollow carbon nanospheres is as follows:

[0017] The hollow carbon nanospheres are placed in a treatment solution at a dosage ratio of 0.05 to 0.15 g / mL and ultrasonically treated for 20 to 30 minutes;

[0018] After filtration, drying, and treating at 540-550° C. for 100-120 min, pretreated hollow carbon nanospheres are obtained;

[0019] The treatment solution is a mixture of a nitric acid solution with a concentration of 60-65% and a sulfuric acid solution with a concentration of 98% in a volume ratio of 1:3.

[0020] The present invention is further configured as follows: the addition amount of the pretreated hollow carbon nanospheres is 7.2-9.8% of the mass of aluminum chloride hexahydrate.

[0021] The present invention is further configured as follows: the surfactant is selected from any one of glyceryl monostearate and polyethylene glycol.

[0022] The second aspect of the present invention: also provides a method for preparing the above-mentioned multifunctional coating material with super hydrophilicity, comprising the following steps:

[0023] Step 1, accurately weighing polyurethane resin, functional additives, synergistic additives, surfactants, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water, and placing the polyurethane resin, functional additives, synergistic additives, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water in a mixing device, and treating at 3200-4200 r / min and 70-80° C. for 40-50 min;

[0024] Step 2: Add a surfactant and process at 1200-1500 r / min and 40-50° C. for 20-30 min;

[0025] Step 3: After the mixing is completed, the materials are discharged, and then inspected and measured to finally obtain a finished product of a multifunctional coating material with super hydrophilicity.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] In the present invention, polyurethane resin, functional additives, synergistic additives, surfactants, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water are used as raw materials. The polyurethane resin, functional additives, synergistic additives, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water are placed in a mixing device for mixing, and then a surfactant is added for treatment. After the mixing is completed, the material is discharged, and then it is inspected and measured to finally obtain a finished product of a multifunctional coating material with super hydrophilicity. The multifunctional coating material with super hydrophilicity prepared by the present invention not only has good super hydrophilicity performance, but also has excellent antibacterial and aging resistance, and effectively guarantees its quality. The multifunctional coating material with super hydrophilicity and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] The present embodiment provides a multifunctional coating material with super hydrophilicity, which is composed of the following raw materials in parts by weight: 30 parts of polyurethane resin, 3 parts of functional additives, 3 parts of synergistic additives, 2 parts of surfactants, 4 parts of sodium dodecyl sulfate, 4 parts of sodium dodecylbenzene sulfonate and 50 parts of water.

[0031] In this embodiment, it should be noted that the polyurethane resin was purchased from Shandong Aodemei Polymer Materials Co., Ltd.

[0032] The preparation process of the functional additive is as follows:

[0033] TEOS was placed in anhydrous ethanol at a mass ratio of 1:2.8, and stirred at 55°C and 100 r / min for 10 min. The compound solution, 25% ammonia water and eugenol were then added to the mixture, and the mixture was stirred for 5 min. The mixture was kept warm for 8 h.

[0034] Then, after centrifugation at a speed of 5200 r / min for 20 minutes, the obtained centrifugal product is washed with anhydrous ethanol for 2 to 4 times, dried and ground to obtain a functional additive.

[0035] Furthermore, the first compound liquid is mixed by γ-aminopropyltriethoxysilane and water in a mass ratio of 1:12, and the addition amount of the first compound liquid is 2.5% of the mass of the mixed liquid.

[0036] The amount of ammonia water added is 2.8% of the mass of the mixed solution, and the amount of eugenol added is 1.8% of the mass of the mixed solution.

[0037] In addition, the preparation process of the synergist is as follows:

[0038] Aluminum chloride hexahydrate was added into deionized water at a dosage ratio of 0.8 g / mL, stirred at 120 r / min for 20 min, and then the pretreated hollow carbon nanospheres were added thereto, and treated at 7000 r / min for 40 min;

[0039] Then, the pH value was adjusted to 8.8 with aqueous ammonia, filtered, washed to neutrality, dried, placed in a nitrogen atmosphere, treated at 880° C. for 14 h, and cooled to obtain a functional additive.

[0040] Furthermore, the preparation process of the pretreated hollow carbon nanospheres is as follows:

[0041] The hollow carbon nanospheres were placed in the treatment solution at a dosage of 0.05 g / mL and ultrasonically treated for 20 min;

[0042] After filtration, drying, and treatment at 540°C for 100 min, pretreated hollow carbon nanospheres were obtained;

[0043] The treatment solution is a mixture of a nitric acid solution with a concentration of 60% and a sulfuric acid solution with a concentration of 98% in a volume ratio of 1:3.

[0044] The addition amount of the pretreated hollow carbon nanospheres is 7.2% of the mass of aluminum chloride hexahydrate.

[0045] In this embodiment, it should be noted that the hollow carbon nanospheres were purchased from Beijing Zhongke Keyou Nanotechnology Co., Ltd.

[0046] Among them, the surfactant is glyceryl monostearate.

[0047] In addition, this embodiment also provides a method for preparing the above-mentioned multifunctional coating material with super hydrophilicity, comprising the following steps:

[0048] Step 1, accurately weighing polyurethane resin, functional additives, synergistic additives, surfactants, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water, and placing the polyurethane resin, functional additives, synergistic additives, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water in a mixing device, and treating at 3200r / min and 70°C for 40min;

[0049] Step 2: Add surfactant and process at 1200 r / min and 40°C for 20 min;

[0050] Step 3: After the mixing is completed, the materials are discharged, and then inspected and measured to finally obtain a finished product of a multifunctional coating material with super hydrophilicity.

[0051] Example 2

[0052] The preparation method of the multifunctional coating material with super hydrophilicity provided in this embodiment is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation method of the multifunctional coating material with super hydrophilicity in this embodiment are different; the specific raw material composition and the specific preparation method of the multifunctional coating material with super hydrophilicity in this embodiment are as follows:

[0053] A multifunctional coating material with super hydrophilicity is composed of the following raw materials in parts by weight: 35 parts of polyurethane resin, 4 parts of functional additives, 4 parts of synergistic additives, 3 parts of surfactants, 5 parts of sodium dodecyl sulfate, 5 parts of sodium dodecylbenzene sulfonate and 55 parts of water.

[0054] In this embodiment, it should be noted that the polyurethane resin was purchased from Shandong Aodemei Polymer Materials Co., Ltd.

[0055] The preparation process of the functional additive is as follows:

[0056] TEOS was placed in anhydrous ethanol at a mass ratio of 1:3, and stirred at 56°C and 110 r / min for 12 min. The compound solution, 25% ammonia water and eugenol were then added to the mixture, and the mixture was stirred for 6 min. The mixture was kept warm for 9 h.

[0057] Then, after centrifugation at a speed of 5300 r / min for 22 minutes, the obtained centrifugal product was washed three times with anhydrous ethanol, dried and ground to obtain a functional additive.

[0058] Furthermore, the first compound liquid is mixed by γ-aminopropyltriethoxysilane and water in a mass ratio of 1:13, and the addition amount of the first compound liquid is 3.2% of the mass of the mixed liquid.

[0059] The amount of ammonia water added is 3.1% of the mass of the mixed solution, and the amount of eugenol added is 2.5% of the mass of the mixed solution.

[0060] In addition, the preparation process of the synergist is as follows:

[0061] Aluminum chloride hexahydrate was added into deionized water at a dosage ratio of 1 g / mL, stirred at 170 r / min for 25 min, and then the pretreated hollow carbon nanospheres were added thereto, and treated at 7500 r / min for 43 min;

[0062] Then, the pH value was adjusted to 9 with ammonia water, filtered, washed to neutrality, dried, placed in a nitrogen atmosphere, treated at 890° C. for 15 h, and cooled to obtain a functional additive.

[0063] Furthermore, the preparation process of the pretreated hollow carbon nanospheres is as follows:

[0064] The hollow carbon nanospheres were placed in the treatment solution at a dosage ratio of 0.1 g / mL and ultrasonically treated for 25 min;

[0065] After filtration, drying, and treatment at 545°C for 110 min, pretreated hollow carbon nanospheres were obtained;

[0066] The treatment solution is a mixture of a nitric acid solution with a concentration of 62% and a sulfuric acid solution with a concentration of 98% in a volume ratio of 1:3.

[0067] The addition amount of the pretreated hollow carbon nanospheres is 8.5% of the mass of aluminum chloride hexahydrate.

[0068] In this embodiment, it should be noted that the hollow carbon nanospheres were purchased from Beijing Zhongke Keyou Nanotechnology Co., Ltd.

[0069] Among them, the surfactant is polyethylene glycol.

[0070] In addition, this embodiment also provides a method for preparing the above-mentioned multifunctional coating material with super hydrophilicity, comprising the following steps:

[0071] Step 1, accurately weighing polyurethane resin, functional additives, synergistic additives, surfactants, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water, and placing the polyurethane resin, functional additives, synergistic additives, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water in a mixing device, and treating at 3700r / min and 75°C for 45min;

[0072] Step 2: Add surfactant and process at 1350r / min and 45°C for 25min;

[0073] Step 3: After the mixing is completed, the materials are discharged, and then inspected and measured to finally obtain a finished product of a multifunctional coating material with super hydrophilicity.

[0074] Example 3

[0075] The preparation method of the multifunctional coating material with super hydrophilicity provided in this embodiment is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation method of the multifunctional coating material with super hydrophilicity in this embodiment are different; the specific raw material composition and the specific preparation method of the multifunctional coating material with super hydrophilicity in this embodiment are as follows:

[0076] A multifunctional coating material with super hydrophilicity is composed of the following raw materials in parts by weight: 40 parts of polyurethane resin, 6 parts of functional additives, 5 parts of synergistic additives, 4 parts of surfactants, 7 parts of sodium dodecyl sulfate, 7 parts of sodium dodecylbenzene sulfonate and 60 parts of water.

[0077] In this embodiment, it should be noted that the polyurethane resin was purchased from Shandong Aodemei Polymer Materials Co., Ltd.

[0078] The preparation process of the functional additive is as follows:

[0079] TEOS was placed in anhydrous ethanol at a mass ratio of 1:3.2, and stirred at 58°C and 120 r / min for 15 min. The compound solution, 25% ammonia water and eugenol were then added to the mixture, and the mixture was stirred for 8 min. The mixture was kept warm for 10 h.

[0080] Then, after centrifugation at a speed of 5400 r / min for 25 minutes, the obtained centrifugal product was washed 4 times with anhydrous ethanol, dried and ground to obtain a functional additive.

[0081] Furthermore, the first compound liquid is mixed by γ-aminopropyltriethoxysilane and water in a mass ratio of 1:14, and the addition amount of the first compound liquid is 4.2% of the mass of the mixed liquid.

[0082] The amount of ammonia water added is 3.5% of the mass of the mixed solution, and the amount of eugenol added is 3.1% of the mass of the mixed solution.

[0083] In addition, the preparation process of the synergist is as follows:

[0084] Aluminum chloride hexahydrate was added into deionized water at a dosage ratio of 1.2 g / mL, stirred at 220 r / min for 30 min, and then the pretreated hollow carbon nanospheres were added thereto, and treated at 8000 r / min for 46 min;

[0085] Then, the pH value was adjusted to 9.2 with ammonia water, filtered, washed to neutrality, dried, placed in a nitrogen atmosphere, treated at 900° C. for 16 h, and cooled to obtain a functional additive.

[0086] Furthermore, the preparation process of the pretreated hollow carbon nanospheres is as follows:

[0087] The hollow carbon nanospheres were placed in the treatment solution at a dosage of 0.15 g / mL and ultrasonically treated for 30 min;

[0088] After filtration, drying, and treatment at 550° C. for 120 min, pretreated hollow carbon nanospheres were obtained;

[0089] The treatment solution is a mixture of a nitric acid solution with a concentration of 65% and a sulfuric acid solution with a concentration of 98% in a volume ratio of 1:3.

[0090] The addition amount of the pretreated hollow carbon nanospheres is 9.8% of the mass of aluminum chloride hexahydrate.

[0091] In this embodiment, it should be noted that the hollow carbon nanospheres were purchased from Beijing Zhongke Keyou Nanotechnology Co., Ltd.

[0092] Among them, the surfactant is glyceryl monostearate.

[0093] In addition, this embodiment also provides a method for preparing the above-mentioned multifunctional coating material with super hydrophilicity, comprising the following steps:

[0094] Step 1, accurately weighing polyurethane resin, functional additives, synergistic additives, surfactants, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water, and placing the polyurethane resin, functional additives, synergistic additives, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water in a mixing device, and treating at 4200r / min and 80°C for 50min;

[0095] Step 2: Add surfactant and process at 1500r / min and 50°C for 30min;

[0096] Step 3: After the mixing is completed, the materials are discharged, and then inspected and measured to finally obtain a finished product of a multifunctional coating material with super hydrophilicity.

[0097] Comparative Example 1: The difference from Example 1 is that in this example, an equal amount of silicon dioxide is used to replace the functional additive.

[0098] Comparative Example 2: The difference from Example 1 is that in this example, an equal amount of aluminum oxide is used to replace the synergist.

[0099] Performance test: The multifunctional coating material samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Examples 1 to 3 and Comparative Examples 1 to 2, respectively; and the relevant properties of the multifunctional coating materials provided in Examples 1 to 3 and Comparative Examples 1 to 2 are tested as follows:

[0100] 1. Contact angle test: The test method is to apply each group of multifunctional coating materials on the glass surface with a thickness of 0.9μm, using the German The contact angle tester (model: DSA-25) produced by the company tests the contact angle of the coating. At room temperature, the water droplet size is set to 5 μL, and a water droplet is dropped on the coating surface. When the contact angle does not change, the reading is taken.

[0101] 2. Antibacterial test: The test method is ISO22196-2011.

[0102] 3. Aging resistance test: Tested in accordance with GB / T1865-1997 standard. The test data are recorded in Tables 1 to 3 below:

[0103] Table 1 Contact angle test results of each group of coating materials

[0104] Group Contact angle (°) Example 1 Group 4 Example 2 Group 5 Example 3 Group 4 Comparison group 1 10 Comparison of 2 groups 12

[0105] Table 2 Antibacterial performance test results of each group of coating materials

[0106] Group Sterilization rate of metallosporins (%) Sterilization rate of Escherichia coli (%) Example 1 Group 99.7 98.5 Example 2 Group 99.5 98.4 Example 3 Group 99.8 98.6 Comparison group 1 95.2 94.9 Comparison of 2 groups 97.6 96.2

[0107] Table 3 Aging resistance test results of each group of coating materials

[0108] Group 2000h hernia anti-aging Example 1 Group No change in appearance Example 2 Group No change in appearance Example 3 Group No change in appearance Comparison group 1 No change in appearance Comparison of 2 groups Appearance has changed

[0109] By comparing and analyzing the relevant data in Tables 1 to 3, it can be seen that the multifunctional coating material with super-hydrophilicity prepared by the present invention not only has good super-hydrophilicity performance, but also has excellent antibacterial and aging resistance, effectively ensuring its quality. This shows that the multifunctional coating material with super-hydrophilicity and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0110] In the present invention, polyurethane resin, functional additives, synergistic additives, surfactants, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water are used as raw materials, and the polyurethane resin, functional additives, synergistic additives, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water are placed in a mixing device for mixing, and then a surfactant is added for treatment. After the mixing is completed, the material is discharged, and then it is inspected and measured to finally obtain a finished product of a multifunctional coating material with super hydrophilicity. The multifunctional coating material with super hydrophilicity prepared by the present invention not only has good super hydrophilicity performance, but also has excellent antibacterial and aging resistance, and effectively guarantees its quality.

[0111] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0112] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A multifunctional coating material with super hydrophilicity, characterized in that: The invention is composed of the following raw materials in parts by weight: 30-40 parts of polyurethane resin, 3-6 parts of functional additives, 3-5 parts of synergistic additives, 2-4 parts of surfactants, 4-7 parts of sodium dodecyl sulfate, 4-7 parts of sodium dodecylbenzene sulfonate and 50-60 parts of water.

2. The multifunctional coating material with super hydrophilicity according to claim 1, characterized in that: The preparation process of the functional additive is as follows: Put tetraethyl orthosilicate in anhydrous ethanol at a mass ratio of 1:2.8-3.2, stir and mix for 10-15 minutes at 55-58°C and 100-120r / min, then add compound liquid, 25% ammonia water and eugenol to the obtained mixture, continue stirring for 5-8 minutes, and keep warm for 8-10 hours; Then, after centrifugation at a speed of 5200-5400 r / min for 20-25 minutes, the obtained centrifugal product is washed 2-4 times with anhydrous ethanol, dried and ground to obtain a functional additive.

3. The multifunctional coating material with super hydrophilicity according to claim 2, characterized in that: The first compound liquid is prepared by mixing γ-aminopropyltriethoxysilane and water in a mass ratio of 1:12-14, and the addition amount of the first compound liquid is 2.5-4.2% of the mass of the mixed liquid.

4. The multifunctional coating material with super hydrophilicity according to claim 2, characterized in that: The amount of ammonia water added is 2.8-3.5% of the mass of the mixed solution, and the amount of eugenol added is 1.8-3.1% of the mass of the mixed solution.

5. The multifunctional coating material with super hydrophilicity according to claim 1, characterized in that: The preparation process of the synergistic aid is as follows: Aluminum chloride hexahydrate was added into deionized water at a dosage ratio of 0.8 to 1.2 g / mL, stirred at 120 to 220 r / min for 20 to 30 min, and then pretreated hollow carbon nanospheres were added thereto, and treated at 7000 to 8000 r / min for 40 to 46 min; Then, the pH value is adjusted to 8.8-9.2 with aqueous ammonia, filtered, washed to neutrality, dried, placed in a nitrogen atmosphere, treated at 880-900° C. for 14-16 hours, and cooled to obtain a functional additive.

6. The multifunctional coating material with super hydrophilicity according to claim 5, characterized in that: The preparation process of the pretreated hollow carbon nanospheres is as follows: The hollow carbon nanospheres are placed in a treatment solution at a dosage ratio of 0.05 to 0.15 g / mL and ultrasonically treated for 20 to 30 minutes; After filtration, drying, and treating at 540-550° C. for 100-120 min, pretreated hollow carbon nanospheres are obtained; The treatment solution is a mixture of a nitric acid solution with a concentration of 60-65% and a sulfuric acid solution with a concentration of 98% in a volume ratio of 1:

3.

7. The multifunctional coating material with super hydrophilicity according to claim 5, characterized in that: The addition amount of the pretreated hollow carbon nanospheres is 7.2-9.8% of the mass of aluminum chloride hexahydrate.

8. The multifunctional coating material with super hydrophilicity according to claim 1, characterized in that: The surfactant is selected from any one of glyceryl monostearate and polyethylene glycol.

9. The method for preparing a multifunctional coating material having super hydrophilicity according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1, accurately weighing polyurethane resin, functional additives, synergistic additives, surfactants, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water, and placing the polyurethane resin, functional additives, synergistic additives, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and water in a mixing device, and treating at 3200-4200 r / min and 70-80° C. for 40-50 min; Step 2: Add a surfactant and process at 1200-1500 r / min and 40-50° C. for 20-30 min; Step 3: After the mixing is completed, the materials are discharged, and then inspected and measured to finally obtain a finished product of a multifunctional coating material with super hydrophilicity.

Citation Information

Patent Citations

  • Super-amphiphobic surface with universality and its preparation method

    CN103709882A

  • High-elasticity exterior wall coating

    CN104761988A

  • Super-hydrophilic coating agent and preparation method thereof

    CN108822712A

  • Preparation method of antibacterial weather-resistant PE / PP plastic

    CN116178845A

  • Surface treatment method for formaldehyde-free and odorless clothing leather

    CN116987830A